ASSOCIATION OF CRITICAL THINKING AND CURRICULUM FOR COLLEGE STUDENTS; A CHALLENGE FOR DEVELOPING COUNTRIES TO ACHIEVE SDG FOUR - Ellahi, Ahtesham; Sharif, Hina (Journal of Ayub Medical College Abbottabad, 2020)
Background: Present challenge for sustainable development goal four is quality of education for all. Critical thinking is the most important skill that an educational institute gives to students and it should be learning outcome at all levels of education. This study aimed to identify critical thinking and its association with curriculum among college students of Rawalpindi, Pakistan. Methods: It was cross-sectional study with 400 college students from federal and Cambridge system selected by multistage random sampling. Structured questionnaire was used with two sections, i.e., demographic and Cornell critical thinking version X. Cronbach's alpha was 0.85. Chi square test of association was used for overall and stratified data for inferential analysis. Results: Study showed that overall, 64% of students had high critical thinking (40.2±10.4). Chi-square test of independence showed significant relation of critical thinking with curriculum, family economic status, being first child, extra-curricular activities, availability of school playground and career counselling services to the students (p-value <0.05). Stratified analysis showed gender and availability of play ground to be associated with critical thinking for federal while for Cambridge system, living with single or both parents, working status of father, sports week and school playground were significantly associated. Conclusion: Overall results suggested that curriculum does have an effect on the critical thinking of students along with facilities available at school. There is need to synergize theoretical and practical approaches in all curriculums to reduce educational inequities. It is needed for growth of our students and to achieve SDG 4 (to ensure inclusive and equitable quality education) in true spirit. Keywords: Critical thinking; Cornell critical thinking tool; Curriculum; Students; Cambridge system; Federal system; Pakistan